Efeito da inseminação artificial transcervical e da aplicação de flunixin meglumine sobre a taxa de prenhez de ovelhas - Rabassa, Viviane Rohrig (2007)
The artificial insemination (AI) with frozen semen in sheep is limited by the high costs of the laparoscopic technique and the variability of the results obtained from transcervical technique. This technique requires attachment of cervix, a procedure that can cause located injuries, further, the extensive uterine manipulation, which can lead to an exacerbated endometrial prostaglandin synthesis, could modify the uterine environment at the moment of conception. The objective of this study was to compare the efficiency of transcervical AI, through the technique of cervix attachment and retraction, in comparison to laparoscopic AI, as well as, to determine the effect of flunixin meglumine application at the moment of AI, on pregnancy rate of ewes, using frozen semen. In fixed-time inseminated ewes, during seasonal anestrous, there was no difference in the pregnancy rate between the transcervical and laparoscopic techniques, which was 40%. In respect to flunixin meglumine, the experiment was carried out during the breeding season and was performed using AI with estrus detection. There was no difference in the pregnancy rate between ewes receiving or not flunixin meglumine (p>0.05), which was 68.9% for the control group and 60.0% for the group that received flunixin meglumine at the moment of transcervical AI. These results were probably due to the minimum manipulation exerted on the cervix of these females, which don t cause injuries that could lead to exacerbated production of embryotoxic substances. Thus, when the transcervical AI technique is carried out through trained inseminators and without extreme manipulation of cervix, it becomes a good alternative for costs reduction in sheep AI, allowing the use of frozen semen in commercial applications.